Detail electrical and dielectric studies on carbon-fly ash composite. (4th March 2017) - Singh, Pratap; Bhattacharya, B.; Singh, Pramod K.
ABSTRACT: A new solid-state composite was prepared by using fly ash as host matrix and carbon shoots of camphor as dispersoid, which are abundantly available and cheap. The composite was characterized by using different techniques. For conductivity and dielectric measurements, we used complex impedance spectroscopy. Maximum conductivity was obtained at 4% of carbon in fly ash. The dielectric measurements affirm conductivity pattern. X-ray diffraction and Fourier transform infrared spectroscopy (FTIR) was conducted which shows composite nature of sample. Total ionic transference number test reveals that conductivity is mainly due to ions.